2019
DOI: 10.1021/acs.jafc.8b05581
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Whole Strawberry Inhibited Colonic Inflammation in Dextran-Sulfate-Sodium-Treated Mice via Restoring Immune Homeostasis and Alleviating Gut Microbiota Dysbiosis

Abstract: Strawberry (Fragaria chiloensis) is a major edible berry with various potential health benefits. This study determined the protective effects of whole strawberry (WS) against dextran-sulfate-sodium-induced colitis in mice. In colitic mice, dietary WS reduced the disease activity index, prevented the colon shortening and spleen enlargement, and alleviated the colonic tissue damages. The abundance of proinflammatory immune cells was reduced by dietary WS in the colonic mucosa, which was accompanied by the suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 43 publications
5
88
0
Order By: Relevance
“…The most important polyphenols groups, mainly founded in fruits, are flavonoids, flavones and flavonols [239]. Accordingly, it has been shown that the intake of whole fruits is a good strategy for the prevention of diseases by increasing the growth of beneficial bacteria (i.e., Bifidobacterium and Lactobacillus) [241], which is in agreement with previous research with pomegranate polyphenol extracts [242] and in animal studies [239].…”
Section: Prevention Of Cardiovascular Diseasessupporting
confidence: 86%
“…The most important polyphenols groups, mainly founded in fruits, are flavonoids, flavones and flavonols [239]. Accordingly, it has been shown that the intake of whole fruits is a good strategy for the prevention of diseases by increasing the growth of beneficial bacteria (i.e., Bifidobacterium and Lactobacillus) [241], which is in agreement with previous research with pomegranate polyphenol extracts [242] and in animal studies [239].…”
Section: Prevention Of Cardiovascular Diseasessupporting
confidence: 86%
“…The DSS‐induced colitis mouse model was used as we previously described . All mice experimental protocols were performed according to the guidelines of the National Institutes of Health guide for the care and use of Laboratory animals, approved by the Ethical Committee of Experimental Animal Center of University of Massachusetts, Amherst (#2014‐0079).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the composition of microbiota in the fecal samples, 16s rRNA sequencing was conducted as previously described. [61] Metagenomics DNA was extracted from the fecal samples utilizing a PowerFecal DNA isolation kit (MoBio Laboratories, Inc., Carlsbad, CA, USA), and the 16s rRNA gene was amplified, uniquely barcoded, and pooled in an equimolar mixture prior to sequencing library construction. The multiplexed library was sequenced on an Illumina MiSeq platform (Illumina, Inc., San Diego, CA, USA).…”
Section: Collection Of Fresh Fecal Samples and Analysis Of Gut Microbmentioning
confidence: 99%
“…Processed colon sections were treated with myeloperoxidase (MPO) antibody for immunohistochemical analysis as previously described. [61] The percentage of positively stained area was measured by ImageJ software. The score system was as follows: percentage of positively stained area: 0, 0%; 1, <25%; 2, 25% to 50%; 3, 51% to 75%, 4, >75%.…”
Section: Quantification Of Fecal Tio 2 In Human and Experimental Mousementioning
confidence: 99%